Lipid Profile of Type 2 Diabetic Patients Attending in a Tertiary Care Medical College Hospital in Dhaka City - Haque, Jakia; Jasmin, Shahana; Farzana, Taposhi (The Journal of Ad-din Women's Medical College, 2023)
Background: Type-2 diabetes mellitus (T2DM) is reported as an independent risk factor for coronary artery disease, which remains 3 to 4-folded riskier for diabetic patients. Previous studies evidenced an association of T2DM with increased risk of cardiovascular diseases (CVDs) which varies among males and females. The present study aims to analyze the lipid profile of T2DM patients and compare the lipid profile of T2DM males and females in Dhaka. Objective: To compare the difference in serum lipid profile between male and female patients suffering from T2DM. Methods: This cross-sectional study was conducted at the Department of Biochemistry, Dhaka Medical College Dhaka. In this study we included 100 diagnosed T2DM patients (male, n= 54 and female, n= 46) aged 21 years and above selected from OPD Dept. of Endocrinology, Dhaka Medical College Hospital (DMCH). Fasting plasma glucose (FPG), Total cholesterol (TC), low density lipoproteincholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C) and triglycerides (TG) concentrations values were estimated by enzymatic method. And, values were analyzed for each group which were subjected for statistical analysis using paired students t-test on SPSS/ Win, V. 22,to identify differences in lipid profiles of diabetic males and females. Prior to start the study ethical permission was taken from Ethical Review Committee of DMCH. Conclusions: Our findings yielded the extent of dyslipidemia among T2DM population remains a major risk factor for CVD, particularly among the T2DM males having higher LDL-C and TG than females. This data suggests that males remain at higher risk to develop CVD than females. The Journal of Ad-din Women's Medical College; Vol. 10 (2), July 2022; p 42-45